A comprehensive study on the relieving effect of Lilium brownii on the intestinal flora and metabolic disorder in p-chlorphenylalanine induced insomnia rats. (31st December 2022) - Si, Yanpo; Wei, Wenjun; Chen, Xiaohui; Xie, Xiaolong; Guo, Tao; Sasaki, Yohei; Zhang, Youbo; Wang, Lili; Zhang, Fei; Feng, Shuying
Abstract: Context: The bulb of Lilium brownii F. E. Brown (Liliaceae) (LB) is a common Chinese medicine to relieve insomnia. Objective: To investigate the molecular mechanism of LB relieving insomnia. Materials and methods: Insomnia model was induced by intraperitoneally injection p -chlorophenylalanine (PCPA) in Wistar rats. Rats were divided into three groups: Control, PCPA (400 mg/kg, i.p. 2 days), LB (598.64 mg/kg, oral 7 days). The levels of 5-hydroxytryptamine (5-HT), norepinephrine (NE), melatonin (MT), and the expression of GABAA, 5-HT1A and MT receptors, as well as pathological changes in hypothalamus, were evaluated. 16S rDNA sequencing and UPLC-MS/MS were used to reveal the change of the intestinal flora and metabolic profile. Results: The adverse changes in the abundance and diversity of intestinal flora and faecal metabolic phenotype altered by PCPA in rats were reversed after LB treatment, accompanied by the up-regulated levels of 5-HT as 8.14 ng/mL, MT as 16.16 pg/mL, 5-HT1A R and GABAA R, down-regulated level of NE as 0.47 ng/mL, and the improvement of pathological phenomena of cells in the hypothalamus. And the arachidonic acid metabolism and tryptophan metabolism pathway most significantly altered by PCPA were markedly regulated by LB. Besides, it was also found that LB reduced the levels of kynurenic acid related to psychiatric disorders and trimethylamine- N -oxide associated with cardiovascular disease. Conclusion: The mechanism of LB relieving insomnia involves regulating flora and metabolites to resemble the control group. As a medicinal and edible herb, LB could be considered for development as a health-care food to relieve increasing insomniacs in the future.